Pengembangan Sistem Informasi Aplikasi Mobile Pelayanan Elektronik Dispendukcapil Kota Malang - Pratama, Dhika Bayu; Armin, Aidil Primasetya (Penerbit Goodwood, 2024)
Purpose: This study aims to develop a mobile application-based public service information system to improve the effectiveness and accessibility of administrative services at the Department of Population and Civil Registration (Dispendukcapil) of Malang City. Research Methodology: This research was conducted at the Dispendukcapil office of Malang City using a descriptive qualitative approach. Data collection methods included field observations, interviews with service users and staff, and analysis of documentation. The mobile application was developed using the Flutter framework and implemented based on the waterfall development model. Results: The resulting application, named SIAPEL, features service registration, real-time document tracking, notifications, and complaint submission via WhatsApp. Testing with 50 respondents showed that 90% found the app easy to use and 86% were satisfied with its interface and usefulness in accessing services. Conclusion: SIAPEL enhances administrative efficiency, reduces service queues, and improves communication between users and the institution. The application has shown positive reception from both users and staff Limitation: The current version only supports Android devices and requires stable internet connectivity for optimal performance. Integration with institutional databases is still being developed. Contribution: This research contributes to the development of mobile-based public service systems, especially in the field of population administration. It can be a reference for other government institutions aiming to implement similar digital services to improve public satisfaction and service efficiency.